The Application of Artificial Lighting in Hotel Room: Grand Anugerah Hotel and Sae inn, Kendal - Ratnasari, Choirunisa; Setiawan, Deni Wahyu; Harsritanto, Bangun I.R. (MAJ - Malaysia Architectural Journal, 2020)
Artificial lighting is inevitable in hotel design. Even though in architecture education, we learn that natural lighting is the top priority, and artificial lighting is supporting in absent of sunlight condition. In the hotel industry, the continuity of the light environment is mandatory to support hotel services. This research aim is to identify the application of lighting types, placements, fittings, and functions in hotel rooms. The methods are literature study, observations, comparative study and analytic descriptions. The case studies were held on two most prominent hotels in Kendal Regency; Central Java named Grand Anugerah and Sae Inn hotels. The results indicated variations of artificial lighting in hotel rooms were related to their styles and functions.